Dietary Supplementation of Novel Aflatoxin Oxidase CotA Alleviates Aflatoxin B1-Induced Oxidative Stress, Lipid Metabolism Disorder, and Apoptosis in the Liver of Japanese Quails - Hao Lv; Zhiyong Rao; Yuting Li; Wei Zhang; Lihong Zhao; Zhixiang Wang; Yongpeng Guo (Animals)
This research explored the role of aflatoxin oxidase CotA in mitigating aflatoxin B1 (AFB1)-induced hepatotoxicity in Japanese quails. A total of 225 female Japanese quails, aged two weeks, were randomly assigned to three dietary groups: a control diet, an AFB1-contaminated diet, and an AFB1-contaminated diet supplemented with aflatoxin oxidase CotA for three weeks. The results indicate that quails receiving the AFB1-contaminated diet exhibited reduced body weight gain, pronounced vacuolar degeneration within hepatocytes, and inflammatory cell infiltration. Additionally, the AFB1 group demonstrated an increased liver index and elevated serum liver enzyme activities (ALT, AST, and ALP). Supplementation with CotA improved body weight gain and conferred protection against AFB1-induced liver injury. Furthermore, the addition of CotA significantly enhanced liver antioxidant enzyme activities (T-AOC, GST, GSH-Px, POD, and CAT), reduced hepatic H2O2 and MDA levels, and upregulated the mRNA expression levels of genes in the Nrf2 pathway in quails exposed to AFB1. AFB1 exposure led to lipid droplet accumulation in liver tissues and elevated serum TG and LDL-C levels. However, the introduction of CotA mitigated AFB1-induced alterations in lipid metabolism. Furthermore, dietary supplementation with CotA inhibited AFB1-induced hepatocyte apoptosis and decreased the mRNA expression of apoptosis-related genes, including Bax, caspase-9, and caspase-3. Notably, the AFB1+CotA group exhibited a significant reduction in AFB1 residues and AFB1-DNA adducts in quail liver tissues compared to the AFB1 group. These findings indicate that aflatoxin oxidase CotA holds promise as a feed additive to alleviate AFB1-induced hepatotoxicity.